Body Composition and Cardiorespiratory Fitness Characteristics Among Female University Students: A Cross-Sectional Study - Mădălina-Gabriela Coman; Andreea Maria Adam; Carmen Gheorghe; Mircea Dan Mocanu; Leonard Stoica; Daniel-Andrei Iordan; Ilie Onu; Dragoș Florin Teodor (Balneo and PRM Research Journal)
Obesity and body composition are crucial indicators of health, especially among young adults whose lifestyle changes during university years can impact physical well-being. This study examines obesity levels and body composition parameters in female university students, hypothesizing that they exhibit elevated body fat percentages compared to health standards, likely due to a sedentary lifestyle. A secondary hypothesis posits a correlation between physical activity levels and body composition, anticipating higher fat mass in students with low physical activity levels. The study included 258 female students, aged 18-23, from seven faculties at the University "Dunărea de Jos" of Galați. Body composition metrics, such as total body water, protein, minerals, body fat mass, skeletal muscle mass, and BMI, were assessed using the InBody 720 (Biospace, Korea). Cardiovascular fitness was evaluated through the Ruffier Test, a widely accepted measure in Europe. SPSS 26 software was used for statistical analysis, applying Skewness and Kurtosis to assess data distribution, while Pearson correlation evaluated relationships between physical activity and body composition. The analysis revealed a significant trend toward elevated fat mass and obesity indicators. The average body fat mass was 32.3%, substantially above the healthy standard of 23%, and 52.3% of participants were classified as having excessive body fat. BMI showed 38% of students in the overweight or obese range. Waist-to-hip ratios highlighted prevalent central adiposity, with a mean of 0.918, exceeding recommended limits for women. A positive correlation was found between lower physical activity and increased fat mass, supporting Hypothesis 2. Findings indicate a high prevalence of obesity-related parameters among female university students, likely linked to lifestyle changes. These results emphasize the importance of health promotion efforts to encourage physical activity and healthy habits in this population, suggesting a role for bioelectrical impedance analysis as a valuable tool in university health assessmentsy